Competencias profesionales demandadas en el mercado laboral peruano - Gutiérrez Villaverde, Herberth Eduardo (2015)
This paper describes the skills most required among professionals within various career paths by leading companies in the Peruvian market, which advertise staffing positions via the weekly magazine Aptitus, part of the newspaper El Comercio, and through other media outlets. This database was created by accumulating results from more than 5,700 job advertisements between 2012 and 2013. By applying multivariate techniques, the job market was identified and the most demanded competencies within professional careers were defined.